Plasminogen-Binding Activity of Neuraminidase Determines the Pathogenicity of Influenza A Virus - Goto, Hideo (American Society for Microbiology, 2001)
When expressed in vitro, the neuraminidase (NA) of A/WSN/33 (WSN) virus binds and sequesters plasminogen on the cell surface, leading to enhanced cleavage of the viral hemagglutinin. To obtain direct evidence that the plasminogen-binding activity of the NA enhances the pathogenicity of WSN virus, we generated mutant viruses whose NAs lacked plasminogen-binding activity because of a mutation at the C terminus, from Lys to Arg or Leu. In the presence of trypsin, these mutant viruses replicated similarly to wild-type virus in cell culture. By contrast, in the presence of plasminogen, the mutant viruses failed to undergo multiple cycles of replication while the wild-type virus grew normally. The mutant viruses showed attenuated growth in mice and failed to grow at all in the brain. Furthermore, another mutant WSN virus, possessing an NA with a glycosylation site at position 130 (146 in N2 numbering), leading to the loss of neurovirulence, failed to grow in cell culture in the presence of plasminogen. We conclude that the plasminogen-binding activity of the WSN NA determines its pathogenicity in mice.